Correlating Cathode Microstructure with PEFC Performance Using FIB-SEM and TEM. Issue 9 (7th July 2017) - Okumura, M.; Noda, Z.; Matsuda, J.; Tachikawa, Y.; Nishihara, M.; Lyth, S. M.; Hayashi, A.; Sasaki, K.
Abstract : The cathode electrocatalyst layers of polymer electrolyte membrane fuel cells (PEFCs) are quantitatively investigated for different ratios of Nafion ionomer. This is achieved using focused-ion-beam coupled scanning electron microscopy (FIB-SEM) to reconstruct the three-dimensional microstructure via tomography. Parameters such as the porosity and pore size distribution were calculated from this data. The distributions of Nafion ionomer, carbon support, and platinum nanoparticles were then further clarified using transmission electron microscopy (TEM). Changes in the PEFC performance (notably the I-V characteristics, the electrochemical surface area, the activation overvoltage, and the concentration overvoltage) are thus correlated to electrode microstructure.